The Influence Of Office Facilities, Work Motivation And Work Discipline On The Performance Of Waihatu Village Officials, Kairatu Sub-District, Seram Bagian Barat District - Semuel Souhoka (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is whether there is an influence of 1) office facilities on the performance of village officials? 2) work motivation on the performance of village officials? 3) work discipline on the performance of village officials? 4) office facilities, work motivation, and work discipline on the performance of village officials. The population in this study were waihatu village officials in Kairatu District, West Seram Regency, totaling 30 people. The population and sample used in this study amounted to 30 people. Data collection methods using questionnaire methods, and documentation. Data analysis techniques using classical assumption analysis and regression. The results showed that there was 1). a positive and significant effect of office facilities on employee performance, according to the results of the first hypothesis test 2). a positive and significant effect of work motivation on employee performance, according to the results of the second hypothesis test. 3). the existence of a positive and significant effect of work discipline on employee performance, according to the results of the third hypothesis test. 4). the existence of a joint influence between office facilities, work motivation and work discipline on employee performance, according to the results of the fourth hypothesis test 5). The contribution of the influence of office facilities, work motivation and work discipline on employee performance (R2) is 95.5%. Work discipline has a greater influence on employee performance.